A Tablet Based Embodied Conversational Agent to Promote Smoking Cessation among Veterans: A Feasibility Study - Abu S Abdullah; Stephan Gaehde; Tim Bickmore (Journal of Epidemiology and Global Health, 2018)
Embodied Conversational Agent (ECA) offer a new means to support smokers as a virtual coach and motivate them to quit smoking. In this study we assess the feasibility and acceptability of an ECA to support quit smoking (“aka ECA-Q”). ECA-Q, a 14-days program, delivered through Tablet computers, interacts with participants with supporting messages for quit smoking and motivates them to set a quit date. Study participants (n = 6) were Veterans receiving medical care at Boston VA Healthcare System who responded to an open advertisement. Participants completed a survey at baseline and after 14 days follow-up. All participants were satisfied with the ECA program and liked the features of the agent; three out of six participants had set a quit date by the end of the 14 days. Participants reported several positive and less important features of the agent and made suggestions to improve the agent. This study shows that a conversation agent is acceptable to smoking veterans to help them in setting a quit date with an ultimate goal of quit smoking. Insights gained from this study would be useful to redesign the current version of ECA-Q program for a future randomized controlled trial to test the efficacy.